IMPACT OF RHIZOBIUM ON GROWTH, BIOMASS ACCUMULATION AND NODULATION IN DALBERGIA SISSOO SEEDLINGS - KUMAR, ANISH; D. DASH,; M. K. JHARIYA, (The Bioscan, 2013)
The present experiment was conducted with six treatments comprised of Dalbergia sissoo-Rhizobium inoculation, 2 levels of N fertilization alone and along with each other including control. Results revealed that root inoculation of D. sissoo seedlings with D. sissoo-Rhizobium inoculum was found significantly effective in improving growth, biomass production and nodulation over only inorganic N application and control. A positive response was found when N in less level was given along with Rhizobium inoculation. Significantly maximum root length (48.2cm), root biomass (17.24 g/seedling) and root/shoot ratio (0.88) were obtained in sissoo seedlings receiving only inoculation at 120 days after transplant (DAT) while combined effect of inoculation along with lower level of N showed maximum seedling height (64.8cm), shoot biomass (20.4 g/seedling) and collar diameter (8.27mm). Significantly maximum nodulation (56/seedling and dry weight 122 mg/seedling) was found in Rhizobium + N1 treatment followed by Rhizobium inoculation only. Root inoculation of D. sissoo seedlings with Rhizobium showed significant effect and further application of N at lower level along with Rhizobium inoculation was found most effective in increasing symbiotic traits and growth performances by D. sissoo seedlings.